Produção de enzimas lignocelulósicas por fermentação em estado sólido por espécimes do gênero Trichoderma para sacarificação do bagaço de cana de açúcar tratado com micro-ondas - Morais, Priscila Atique de [UNESP] (2015)
This study was divided in two steps, the first investigated the production of lignocelullosic enzymes for specimens of Trichoderma cultivated by state solid fermentation under different conditions physical-chemical. For ten specimens available, four showed satisfactory results of enzymatic production, being identified three species. T. virens, T. harzianum e T. aspereloides). The greatest production of CMCase (23 U/g), was obtained by T. asperelloides and the greatest production of β-glicosidase (4U/g) and xilanase (1640U/g) were obtained by T. virens. In the second investigation, was tested the efficiency of pre-treatment of bagasse sugar cane with microwave radiation in presence of acid phosphoric (0.05M), sodium hydroxide (0.01M), glycerol (10%) all diluted in water in fiber structure. About the treatments of the bagasse, the most efficient in the liberation of phenolic compounds (4.24 mg/g) and reducing sugars (0.06±0 mg/g) was the solution in microwave with NaOH and glycerol, respectively. The dry weight results after the treatment were significant, with a maximum of 14% loss of the initial in treatment with NaOH. The thermogravimetry and morphological analysis of treated bagasse with a microwave and NaOH, showed changes in the structure of the material showing the effectiveness of treatment in biomass breakdown